The Analysis Of Broiler Price Fluctuations in Indonesia - Fitrimawati, Fitrimawati; Nurhayati, Nurhayati; Indrayani, Ida; Qamara, Cori (JURNAL ILMIAH PETERNAKAN TERPADU, 2024)
The broiler industry condition nationally is facing an obstacle. It is often appearance an increase in production input cost, at the same time, it is also happened a decrease in the price of livebird as production output. This research purpose is, to analyzes factors what influence the broiler price fluctuations in Indonesia. Data  processed in this research is a secondary data from Indonesian Statistics Agency. The used analysis is a panel data regression to know about the effects of feed and  day old chicken (DOC) prices, the demand and supply on the broiler chickens. Data were collected from the time series data and cross section data, namely for five years each provinces. The data were collected from 34 provinces in Indonesia. The research result is found that the feed price, the Doc price and the broiler supply get significant effect on the broiler price. So the broiler demand no effected in the broiler chicken prices.